MATH SOLVE

2 months ago

Q:
# I have 2 questions that I need help with. Thank you for helping.

Accepted Solution

A:

r^2=(x−h)^2+(y−k)^2

(-2, 6) and (-2, 10)

r^2 = (10 - 6)^2 + (-2+2)^2

r^2 = 4^2

r^2 = 16

answer is A.

(x +2)^2 + (y - 6)^2 = 16

--------------------

r^2=(x−h)^2+(y−k)^2

(1,2) and (0,6)

r^2 = (6-2)^2 + (0-1)^2

r^2 = 4^2 + 1^2

r^2 = 17

answer is C.

(x - 1)^2 + (y - 2)^2 = 17

--------------------

(-2, 6) and (-2, 10)

r^2 = (10 - 6)^2 + (-2+2)^2

r^2 = 4^2

r^2 = 16

answer is A.

(x +2)^2 + (y - 6)^2 = 16

--------------------

r^2=(x−h)^2+(y−k)^2

(1,2) and (0,6)

r^2 = (6-2)^2 + (0-1)^2

r^2 = 4^2 + 1^2

r^2 = 17

answer is C.

(x - 1)^2 + (y - 2)^2 = 17

--------------------